Scientific Objectivity and the Pursuit of the Public Good. - Hundemer, Sadie; Loizzo, Jamie; Peterson, Anna L.; Stoutamire, Stephanie; Paxson, S. B. (Science & Engineering Ethics, 2026)
Scientists are increasingly expected to not only produce objective science but also to use their science and expertise to support the public good. Prior studies indicate that scientists see both responsibilities as important; however, it is not clear how scientists manage these responsibilities when they are perceived to be in tension. In this study, scientists at land-grant institutions (n = 87) were presented with binary choices to identify where tensions may exist and how scientists make decisions between competing responsibilities. We examined nine categories of potential tensions: direct conflicts between objectivity and public impact, engagement in public outreach, communication priorities and approach, political engagement and perceived bias, the media, funding and disclosure, supporting/protecting specific causes, diversity, and ethical decision making. Results indicate that scientists belong to three cultures of ethical thought: arbiters, advocates, and brokers. These cultures roughly align with the scientist roles described by Pielke and suggest different prioritizations of commitment to public service relative to commitment to objective science, though both commitments were valued. There was variation across cultures of thought on whether scientists should openly support policies based on their research. Broad areas of agreement across cultures of thought were also identified. Scientists of all cultures of thought indicated a willingness to see themselves in a public role, communicating openly with non-experts on issues where scientific research intersects with the public good. There was also an expressed need for scientists to receive better training and tools to manage conflicting responsibilities.